Efektivitas Program Pembebasan Pokok dan Sanksi Administrasi Pajak Kendaraan Bermotor dalam Rangka Meningkatkan Pad Kabupaten Bungo Provinsi Jambi - FAJAR DOLLY (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2026)
This study aims to determineeffectiveness of the motor vehicle tax amnesty programin order to increase PAD of Bungo Regency, Jambi Province. The research method used in this study was qualitative with a descriptive approach. The sample was selected using direct sampling and random sampling techniques, with 12 individuals from among taxpayers. Meanwhile, the data analysis technique used the interactive approach of Miles and Huberman, which consists of data collection, data reduction, data presentation, and conclusion drawing/verification. Based on the research results, it can be seen that the level ofThe effectiveness of the motor vehicle tax amnesty program in order to increase PAD at the Joint Samsat Office of Bungo Regency is still not effective.. Obstacles facedin the Joint Samsat Office of Bungo Regency in implementing the two-wheeled motor vehicle tax amnesty program, including:limited infrastructure of mobile SAMSAT cars and ineffective time and location points of mobile SAMSAT car services; Lack of preventive and repressive actions by Bungo Regency Joint SAMSAT Office Officers towards taxpayers; short implementation timetwo-wheeled motor vehicle tax amnesty program.Efforts made to overcome these obstacles include: Improving Mobile SAMSAT Vehicle Facilities and Infrastructure and adding more locations or service times for Mobile SAMSAT Vehicles; Increasing Preventive and Repressive Actions by Bungo Regency Joint SAMSAT Office Officers towards Taxpayers; Extending the Implementation TimeMotor Vehicle Tax Amnesty Program